Synthesis, Antiproliferative Activity and Molecular Docking Studies of 1,3,5-Triaryl Pyrazole Compound as Estrogen α Receptor Inhibitor Targeting MCF-7 Cells Line - Noval Herfindo; Riska Prasetiawati; Daniel Sialagan; Neni Frimayanti; Adel Zamri (Universitas Jenderal Soedirman, 2020)
This research has been successfully synthesized three compounds of 1,3,5-triaryl pyrazole derivatives by two steps reaction. Firstly, pyrazoline (4a-c) compound was obtained by one-pot reaction of aromatic ketones, aldehyde and hydrazine in basic condition. Then, pyrazole (5a-c) compound was obtained by oxidative aromatization of compound 4 in the presense of acetic acid. Chemical structure of predicted molecules was confirmed by FTIR, NMR and HRMS spectroscopy data analysis. Antiproliferative activity of compound 5a-c were evaluated by in vitro assay against MCF-7 cells line and molecular docking simulation against ERα (PDB ID: 3ERT) using MOE 2019. Biological evaluation result showed that pyrazole compounds had weak antiproliferative activity against MCF-7 cells with IC50 were > 1000 µM, whereas the docking studies agrees the result.